ChemInform Abstract: High Q Ceramics in the ACe2(MoO4)4 (A: Ba, Sr, and Ca) System for LTCC Applications. Issue 10 (7th March 2013) - Surjith, A.; Ratheesh, R.
Abstract The new title ceramics are prepared from mixtures of MCO3 (M: Ba, Sr, and Ca), CeO2, and MoO3 (815—830 °C, 1 h) and characterized by powder XRD, SEM, Raman spectroscopy, and dielectric measurements.